Soft computing methods for system dependability - Mellal, Mohamed Arezki (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2020)
"This book explores the development and applications of soft computing methods in solving system dependability problems"--Provided by publisher.